GABBR1 monoallelic de novo variants linked to neurodevelopmental delay and epilepsy - Cediel, Maria Lucia; Stawarski, Michal; Blanc, Xavier; Nosková, Lenka; Magner, Martin; Platzer, Konrad; Gburek-Augustat, Janina; Baldridge, Dustin; Constantino, John N; Ranza, Emmanuelle; Bettler, Bernhard; Antonarakis, Stylianos E (American journal of human genetics, 2022)
GABAB receptors are obligatory heterodimers responsible for prolonged neuronal inhibition in the central nervous system. The two receptor subunits are encoded by GABBR1 and GABBR2. Variants in GABBR2 have been associated with a Rett-like phenotype (MIM: 617903), epileptic encephalopathy (MIM: 617904), and milder forms of developmental delay with absence epilepsy. To date, however, no phenotypes associated with pathogenic variants of GABBR1 have been established. Through GeneMatcher, we have ascertained four individuals who each have a monoallelic GABBR1 de novo non-synonymous variant; these individuals exhibit motor and/or language delay, ranging from mild to severe, and in one case, epilepsy. Further phenotypic features include varying degrees of intellectual disability, learning difficulties, autism, ADHD, ODD, sleep disorders, and muscular hypotonia. We functionally characterized the four de novo GABBR1 variants, p.Glu368Asp, p.Ala397Val, p.Ala535Thr, and p.Gly673Asp, in transfected HEK293 cells. GABA fails to efficiently activate the variant receptors, most likely leading to an increase in the excitation/inhibition balance in the central nervous system. Variant p.Gly673Asp in transmembrane domain 3 (TMD3) renders the receptor completely inactive, consistent with failure of the receptor to reach the cell surface. p.Glu368Asp is located near the orthosteric binding site and reduces GABA potency and efficacy at the receptor. GABA exhibits normal potency but decreased efficacy at the p.Ala397Val and p.Ala535Thr variants. Functional characterization of GABBR1-related variants provides a rationale for understanding the severity of disease phenotypes and points to possible therapeutic strategies.
Keywords: Epilepsy; epilepsie; HEK293 Cells; Intellectual Disability; Receptors, GABA-B; Neurodevelopmental Disorders; mentální retardace; neurovývojové poruchy; receptory GABA-B; HEK293 buňky; Humans; GABBR1; gene; mendelian disease; Nervous System Malformations; GABA; gamma-Aminobutyric Acid; malformace nervového systému; lidé